VILLAGE PERFORMANCE IN SOCIETY EMPOWERMENT AT MERJOSARI VILLAGE LOWOKWARU DISTRICT MALANG CITY - Kogoya, Yali; Sholahuddin, Agus; Sadhana, Kridawati (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Performance is a describe about implementation of accomplishment level a policy in making atarget, goal, mission and vission of organization that poured forth planning strategy an organization.Performance terminology often to used to state about achievement or individual success level although agroup with have a success criteria that already made before.Village is village chief workspace area as a part of territory/city or under district, based onMalang Mayor Regulation Number 71 2008 Year About Basic Duty, Fungtion, and Village SystemManagement, related with that, so village can not get loose from so many policy that has taken by citygovernment (include founding and providing). And the consequence of that thing, the villagegovernment demanded to have a better skill to answer duty challenge that will harder at the future.So that’s why, we need a serious attention from many sides to providing society, to improve theperformance, here Merjosari Village Lowokwaru District Malang City in function to support and kickalso realize program as a shape of good performance.Cause the demand of society needed, so it’s often to be happen unsatisfied of society, because abad performance that shows from government. In this research investigate about performance of villageagency based on basic duty and village system management.This research use quantitative research method and measured use likert scale with focused onproductivity, service quality, responsibility, and accountability, based on basic duty and village fungtion.From the result of that four indicator research, the writer conclude that Merjosari Village Governmentstill have to do repairing.